Comparison of corrosion behaviour and passive film properties of 316L austenitic stainless steel in CO2 and N2 environments - Abdulwahhab, Y.; Pojtanabuntoeng, Kod; Kinsella, B.; Veder, Jean-Pierre; Barifcani, Ahmed (Maney Publishing, 2019)
This study investigated the susceptibility to pitting corrosion of 316L in CO2and N2environments at temperatures from 30 to 80°C in 3 wt-% NaCl at pH 4. Results from cyclic polarisation technique confirm greater pitting susceptibility of 316L in the CO2environment. Electronic properties and composition of the passive film were identified by electrochemical impedance spectroscopy, Mott–Schottky, and X-ray photoelectron spectroscopy. Increasing temperature negatively affects the passive film stability, and its influences are amplified in the presence of CO2as compared to N2. In the CO2environment, the passive film becomes porous with the increasing temperature leading to higher defects (donor/acceptor densities).